IMPLEMENTASI HAK ROYALTI LAGU UNTUK KEPENTINGAN KOMERSIAL (Studi di Radio Republik Indonesia Madiun) - Rayhan Muzakki Rayhan (Fakultas Hukum Universitas Islam Malang, 2022)
ABSTRACTThe development of music in Indonesia from year to year is getting bigger. Based on the description contained in the background of the problem, the following problems can be formulated: the realization of collecting song royalties for commercial purposes on Radio Republik Indonesia Madiun, an effort by the National Collective Management Institute (LMKN) in order to impose sanctions on broadcasting institutions that violate the provisions of the Copyright Law. this is juridical empirical. The approach used in this research is sociological juridical, Implementation of the Application of Song Royalty Rights for Commercial Interests. The realization of royalty collection at RRI Madiun has been implemented and related to royalty collection can only be done for commercial purposes that use songs as backsound for commercial purposes, for example baby shark to Buy shopee. The efforts of the National Collective Management Institute (LMKN) are currently not running because broadcasting is still under the auspices of KPI.Keywords: Implementation of Royalty Rights, Commercial Interest ABSTRAKPerkembangan musik di Indonesia dari tahun ke tahun semakin besar. Berdasarkan uraian yang terdapat dalam latar belakang masalah, dapat dirumuskan permasalahan berikut: realisasi pemungutan royalti lagu untuk kepentingan komersial pada Radio Republik Indonesia Madiun upaya Lembaga Menejemen Kolektif Nasional (LMKN) dalam rangka menjatuhkan sanksi bagi lembaga penyiaran yang melanggar ketentuan UU Hak Cipta.Jenis penelitian ini adalah yuridis empiris. Pendekatan yang digunakan dalam penelitian ini adalah bersifat yuridis sosiologis, Implementasi Penerapan Hak Royaltiy Lagu Untuk Kepentingan Komersiel.Realisasi pemungutan royalty di RRI Madiun sudah diterapkan dan terkait dengan pemungutan royalti hanya dapat dilakukan untuk kepentingan komersial yang menggunakan lagu sebagai backsound untuk kepentingan komersial tersebut contohnya baby shark menjadi Beli shopee.Upaya lembaga Lembaga Manajemen Kolektif Nasional (LMKN) saat ini belum berjalan karena penyiaran masih dibawah naungan KPI.